Improving peer relationships : achieving results informally - Hill, Norman C. (Crisp Pub. Menlo ParkUS, 1996)
Explains why organizational peer relationships are important; discusses techniques of good peer relationships; and points out problems in these relationships. Deals with topics including: the thirteenth fairy; avoiding actions that irritate your peers; and resolving differences among peers.